Revisiting agricultural input and farm support subsidies in Africa: The case of Ghana’s mechanization, fertilizer, block farms, and marketing programs - Benin, Samuel; Johnson, Michael E.; Abokyi, Emmanuel; Ahorbo, Gerald; Jimah, Kipo; Nasser, Gamel; Owusu, Victor; Taabazuing, Joe; Tenga, Albert (International Food Policy Research Institute, 2013)
Use of agricultural input and farm support subsidies in Africa has returned strongly to the development agenda, particularly following the recent high food and input prices crisis. Many of the donors who opposed them in the past and subsequently put pressure to discontinue them due to their high cost and distortionary effect on the domestic economy are now providing aid in the form of farm support and agricultural subsidies. In Ghana, for example, the country of study in this paper, the government has since 2007 introduced four major subsidy and support programs on fertilizer, mechanization, block farms, and marketing. Therefore, a key question that arises is how the structure and policies of these current programs account for any of the general lessons and controversies experienced in the past and, in the process, achieve their intended goals in a more effective and economically viable manner.